Closing innovation and intellectual property diversity gaps : a global literature review - Carpentier, Élodie; Brant, Jennifer; Bahl, Utsav; Kanellia, Aikaterini (World Intellectual Property Organization, 2024)
"Innovation is a driver of competitive advantage and economic growth, with patent rights playing a critical supporting role. However, differential access to patent rights and relatively less participation in innovation can affect women and people from other historically underrepresented groups, thereby hindering progress and limiting the potential economic benefits generated by innovation. This paper reviews the global literature on these "diversity gaps", identifies their key drivers, and documents international policies and initiatives that show promise in addressing them. Building upon Shapanka and Fechner (2018), it expands the geographic scope and reinforces the scientific basis of their analysis. The paper also provides recommendations for a wide range of stakeholders and offers insights for fostering more inclusive and equitable innovation ecosystems."-- Provided by publisher
"May 21, 2024"--Page 1.
Keywords: Intellectual property.; Technological innovations.; Patent laws and legislation.; Inventors.; Minorities in technology.; Minorities in science.; Minorities in engineering.; Minorities in mathematics.; Minority business enterprises.